Uma avaliação do serviço de atenção domiciliar/programa melhor em casa: o caso do hospital Monsenhor Walfredo Gurgel - Rodrigues, Francenildo Dantas (2013)
This dissertation try to understand how management actions implemented by Monsenhor Walfredo Gurgel Hospital in the city of Natal promote effectively the benefits of Home Care Services / Programa Melhor em Casa . The research is exploratory and descriptive, qualitative approach. Data were collected through document analysis and the interviews with the managers of the Program in Health Department and Hospital beyond the questionnaires with the home care teams and technical management unit of Hospital Jobs. The information were treatment trough categories that analyzed to implemented actions and program objectives. The results show that: the practices carried out by the host teams produce the humanization of care by seeking to ensure access to health services and solving human form; networks of health care are not yet finalized hindering the referral of patients to other units, the networks allow support from other institutions to minimize the problems encountered, the management unit vacancies allows the reduction of costs, mainly by regulating beds and record of health initiatives in home care assists in the monitoring and evaluation process of the Services Home Care / Programa Melhor em Casa primarily the epidemiological profile and patients individual treatment plan. Concludes that most of the actions implemented by the Hospital contribute to the effectiveness of the goals of Programa Melhor em Casa